Rancang Bangun Aplikasi Perencanaan Pembelajaran Dan Penilaian Harian Untuk Sekolah Dasar Menggunakan Kurikulum 2013 - Saputra, Resi Mairapon; Widodo, Arifin Puji; Patia, Romeo (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2017)
In the academic year 2014/2015 the government to implement the curriculum 2013 simultaneously to all schools in Indonesia. But in the academic year 2015/2016 as much as 94% of school back into the curriculum KTSP and 6% schools that still use the curriculum 2013. And in the academic year 2016/2017 increased 19% schools using the curriculum 2013. Emerging problems of schools that have not been fully used curriculum 2013 until the academic year 2016/2017 due for schools and teachers are not ready and are still difficulties in implementing curriculum 2013. the curriculum 2013 was developed in the modern era where sophisticated era of information technology. Administrative procedure of making the curriculum 2013 is designed to be operated using the information system. However there is no information system that assist schools in making administrative procedures curriculum 2013.From the above problems, then made a planning application daily learning and assessment for primary schools using the curriculum 2013 to assist and guide the teachers in designing lesson plans, create lesson plans and assessment in accordance with the daily lesson plan.Based on trial results, applications are made to assist and guide teachers in planning a lesson plan, lesson plan and make an assessment made daily according to RPP. This application can generate a calendar of education, analysis of effective days, the annual program, the semester program, learning schedule, basic competence mapping, setting KKM, RPP, and daily assessment.Â Keywords: Lesson Planning, Daily Assessment, Curriculum, 2013